2015
DOI: 10.1308/rcsann.2015.0008
|View full text |Cite
|
Sign up to set email alerts
|

The role of WNT signalling in urothelial cell carcinoma

Abstract: Urothelial cell carcinoma (UCC) of the bladder is one of the most common malignancies, causing considerable morbidity and mortality worldwide. It is unique among the epithelial carcinomas as two distinct pathways to tumourigenesis appear to exist: low grade, recurring papillary tumours usually contain oncogenic mutations in FGFR3 or HRAS whereas high grade, muscle invasive tumours with metastatic potential generally have defects in the pathways controlled by the tumour suppressors p53 and retinoblastoma. Over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…For instance, The Cancer Genome Atlas (TCGA) Research Network detected Wnt signaling alterations in 73% of UCC tumors [ 35 ]. However, Ahmad et al noted Wnt signaling in only 33% of their clinical UCC samples [ 36 , 37 , 38 ]. The discrepancy could most likely be due to comparisons using different methods and patient populations.…”
Section: Upregulation Of Wnt/β-catenin In Bladder Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, The Cancer Genome Atlas (TCGA) Research Network detected Wnt signaling alterations in 73% of UCC tumors [ 35 ]. However, Ahmad et al noted Wnt signaling in only 33% of their clinical UCC samples [ 36 , 37 , 38 ]. The discrepancy could most likely be due to comparisons using different methods and patient populations.…”
Section: Upregulation Of Wnt/β-catenin In Bladder Carcinogenesismentioning
confidence: 99%
“…For example, one Ahmad et al study used a tissue microarray array with core biopsy samples, whereas a TCGA study detected aberrations in Wnt signaling through genomics using RNA-seq and whole exome sequencing [ 35 , 36 , 37 , 38 ]. Also there was a difference in sample size with TCGA and Ahmad et al studies using 131 and 60 patient samples respectively [ 35 , 36 , 37 , 38 ]. Additionally it was noted that β-catenin expression’s correlation to tumor grade and muscle invasion has been inconsistent [ 39 ].…”
Section: Upregulation Of Wnt/β-catenin In Bladder Carcinogenesismentioning
confidence: 99%
“…Knockdown of LETM1 inhibits the activation of the Wnt/β-catenin pathway. Some evidence has indicated that the Wnt/β-catenin pathway plays a critical role in the tumor progression and metastasis of human bladder cancer cells (11,12). To further explore the effects of si-LETM1 on the Wnt/β-catenin signaling pathway in human bladder cancer cells, we determined the protein expression of β-catenin, cyclin D1 and c-Myc when knocking down LETM1.…”
Section: Knockdown Of Letm1 Inhibits Bladder Cancer Cell Migration Anmentioning
confidence: 99%
“…Therefore, the Wnt signaling pathway participates in each of the stages of malignant cancer development and clearly contributes to human tumor progression. Much research has been reported on the relationship between Wnt signaling pathways and urological cancers (including bladder cancer) [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%